Advanced Teaching Methods and Strategies - Rasulova Muhabbat Ixtiyorovna (Genius Publishing Group, 2023)
This article presents various methods and methods used in learning foreign languages. In the lesson, it is determined that the main task is to teach the language in the case of their interest using various methods when working with students.
Keywords: individual learning; group learning; open-ended questionnaire; picture description